Print culture histories beyond the metropolis - Felsenstein, Frank; Hall, Kenneth R; Hall, Robert G. (Robert Gaston), 1958- (Studies in book and print culture., 2016)
"Bringing together leading scholars of literature, history, library studies, and communications, Print Culture Histories Beyond the Metropolis rejects the idea that print culture necessarily spreads outwards from capitals and cosmopolitan cities and focuses attention to how the residents of smaller cities, provincial districts, rural settings, and colonial outposts have produced, disseminated, and read print materials. Too often print media has been represented as an engine of metropolitan modernity. Rather than being the passive recipients of print culture generated in city centres, the inhabitants of provinces and colonies have acted independently, as jobbing printers in provincial Britain, black newspaper proprietors in the West Indies, and library patrons in "Middletown," Indiana, to mention a few examples. This important new book gives us a sophisticated account of how printed materials circulated, a more precise sense of their impact, and a fuller of understanding of how local contexts shaped reading experiences."--